The Almost Split Sequences for Trivial Extensions of Hereditary Algebras (Communications in Mathematical Research, 2021)
Let $A$ be a basic hereditary artin algebra and $R = A \ltimes Q$ be the trivialextension of $A$ by its minimal injective cogenerator $Q$. We construct some right (left)almost split morphisms and irreducible morphisms in mod$R$ through the corresponding morphisms in mod$A$. Furthermore, we can determine its almost split sequencesin mod$R$.